Собственные формы и частоты плоских колебаний закрепленного упругого кольца - Закржевский, А.Е.; Ткаченко, В.Ф.; Хорошилов, В.С. (Прикладная механика, 2010)
The modes and frequencies of natural vibrations of elastic ring are determined numerically within the framework of the boundary problem for corresponding differential operator of the 6th order. The ring is fixed at one point and models a large ring antenna, which slowly increases in sizes in conditions of weightlessness. The bending vibrations in the ring plane are considered. The numerical results are given. В рамках крайової задачі для відповідного диференційного оператора 6-го порядку чисельно визначено частоти та форми власних коливань пружного кільця, що закріплене в одній точці. Кільце моделює велику кільцеву антену, що повільно збільшує свій розмір у стані невагомості. Розглянуто згинні коливання в площині кільця. Наведено результати розрахунків.